Consumer Attitude Towards Online Shopping of Apparels - Zaid, Jamil A. A.; KHALED, Amgad S. D; Thabit, Ali (The Eastasouth Management and Business, 2023)
Objective: The objective of this study is to investigate the perspective of shoppers towards the online purchase of clothing items. The research aims to identify the factors that influence consumers in the realm of electronic commerce, and to examine the correlation between e-satisfaction and e-loyalty. Given that the internet has emerged as a platform for conducting online transactions, it is imperative for companies to comprehend the consumer perception of online shopping and to determine the marketing strategies that can be employed to attract consumers. Methodology: Quantitative data was generated on the basis of the research instrument (Questionnaire) to test the research hypothesis. The date gathering was carried out by the survey which was sent online to 200 rand only reflected consumer is from which 101 responded. The data has been analysed through SPSS software. Finding: This study identifies what the factors influencing the online shopping decision of students research has shown an interest in investigating consumer motivations that affect the online shopping behaviour the objective of this study is to measure the student perception on different factors relate to online shopping which motivates the student to decide or not to decide to buy online.